PENGARUH BUDAYA SEKOLAH, SARANA PRASARANA DAN KUALITAS LAYANAN TERHADAP EFEKTIVITAS SISTEM INFORMASI MANAJEMEN SEKOLAH DI SMA MUHAMMADIYAH 1 DAN SMA MUHAMMADIYAH 2 YOGYAKARTA (JURNAL ILMIAH TUT WURI HANDAYANI, 2014)
The Influence of School Culture, Facility, and the Quality of Services on the Effectiveness of School Management Information System at Senior High School Muhammadiyah 1 and Senior High School Muhammadiyah 2 Yogyakarta. This study was aimed to investigate the influence of school culture, facility, and the quality of services, individually or collectively on the effectivity of school management information system at SMA Muhammadiyah 1 and SMA Muhammadiyah 2 Yogyakarta. The population of the study was 1847 students. The number of the sample was gainedbased on Harry King nomogram was 332 students. In this study, the writer used the proportional stratified random sampling technique. For the data gathering, the writer used a questionnaire with a Likert Scale. The data gathered then were analyzed by using the software of Statistical Package for Social Science(SPSS) version 16. The technique used for testing the hypothesis was the multipleregression analysis with three predictors and partial correlation on 5% significance.The results of the study showed that (1) School culture, facility, and the quality of service had positive and significant influence to effectivity of school management information system. (2) School culture had positive and significant influence to effectivity of schoolmanagement information system. (3) Facility had positive and significant influence to effectivity of school management information system. (4) The quality of service had positive and significant influence to effectivity of school management information system. The total of effective contribution was 39.86% which meant that there were other factors of 60.14% out of the school culture, facility, and quality of services which influenced the effectivity of school management information system. From the effective contribution, the variable of school facility has provided the highest contribution which was followed by school facility and the quality of services.